Some Issues of Normative and Legal Regulation of Weapons in Ukraine - K. L. Buhaichuk (Bulletin of Kharkiv National University of Internal Affairs, 2021)
The author of the article studies the current state of legal regulation of civilian firearms turnover in Ukraine. The content of the bills that had been submitted to the Verkhovna Rada of Ukraine at the end of 2020 was analyzed: «On the circulation of civil firearms and ammunition for them» (No. 4335), «On civilian weapons and ammunition» (No. 4335-1), «On the introduction amendments to the Code of Ukraine on Administrative Offenses and the Criminal Code of Ukraine to implement the provisions of the Law of Ukraine "On the circulation of civil firearms and ammunition for them"» (No. 4336), «On Amending the Code of Ukraine on Administrative Offenses and the Criminal Code of Ukraine to implement the provisions Of the Law of Ukraine "On civilian weapons and ammunition"» (No. 4336-1). The author has formulated his own scientific position in regard to granting citizens the right to carry and use short-barreled firearms.